2020
DOI: 10.21203/rs.2.23628/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice of healthcare workers towards Hepatitis B virus infection in Mogadishu, Somalia: A Cross-Sectional Study

Abstract: Background Hepatitis B virus (HBV) infection is globally distributed with its attendant complications such as chronic hepatitis, liver cirrhosis and hepatocellular carcinoma. Somalia is among the countries with high prevalence of HBV infection. This study aims to assess the knowledge, attitude and practice (KAP) of healthcare workers (HCW) towards HBV infection in Mogadishu, Somalia. Methods The cross-sectional study was conducted on HCW to assess KAP towards HBV infection. Standardized questionnaires were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
2
2
3
Order By: Relevance
“…Our study reveals that 69.7% of HCWs had good knowledge about HBV infection. This percentage is lower compared to that reported in a recent study performed in Mogadishu, where 80.9% of the HCWs had a good knowledge of HBV [ 26 ]. Likewise, our result is lower than that of a study conducted in Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria, which reported a percentage of 78.2% [ 27 ].…”
Section: Discussioncontrasting
confidence: 69%
“…Our study reveals that 69.7% of HCWs had good knowledge about HBV infection. This percentage is lower compared to that reported in a recent study performed in Mogadishu, where 80.9% of the HCWs had a good knowledge of HBV [ 26 ]. Likewise, our result is lower than that of a study conducted in Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria, which reported a percentage of 78.2% [ 27 ].…”
Section: Discussioncontrasting
confidence: 69%
“…Based on our study majourty of study participants, 279 (65.6%) had good knowelege towards HBV infection. This finding was inconsistance with the study done in Mogadishu Somalia (80.9%) [ 12 ], Northern Nigeria (76.9%) [ 6 ], and khartoum, Sudan (70.0%) [ 13 ], respectively. This is maybe the difference in the educational status of the study population.…”
Section: Discussioncontrasting
confidence: 85%
“…This study showed that medical laboratory professionals (70%) answered correctly with practice questions followed by pharmacy professionals (68.7%), psychiatrists (50%), radiographers (33.3), and medical doctors (32.2%), respectively. In this study of 158 (37.4%), study participants were screened for HBV; however, the majority of 255 (60.4%) health care workers had vaccinated against HBV which is lower than the study was done in Mogadishu, Somalia (83.7%); in this study finding related to screeing for HBV and vaccination against the infection were 86.3% [ 12 ]. This is may be as a result of shortage of screening kits and vaccination in this study area.…”
Section: Discussionmentioning
confidence: 85%
“…Penelitian di Somalia tidak hanya melibatkan analis kesehatan, namun juga dilakukan pada dokter dan perawat. 15 Begitu juga halnya dengan penelitian yang dilakukan di Nigeria Utara dengan responden dokter, perawat, apoteker dan analis kesehatan. 16 Penelitian di Cameroon menyebutkan bahwa jenis pekerjaan memiliki hubungan yang signifikan dengan pengetahuan dan sikap tenaga kesehatan tentang hepatitis B (p<0,05).…”
Section: Hubungan Antara Pengetahuan Dengan Sikap Respondenunclassified
“…17 Hasil yang berbeda ditemukan pada penelitian di Somalia yang menunjukkan bahwa terdapat hubungan yang signifikan antara pengetahuan dengan praktik tenaga kesehatan (p<0,05). 15 Perbedaan ini diperkirakan terjadi karena adanya perbedaan dari jenis pekerjaan. Penelitian di Somalia dilakukan pada 430 responden yang terdiri atas dokter, perawat dan analis kesehatan.…”
Section: Hubungan Antara Pengetahuan Dengan Praktik Respondenunclassified